Messianic Hope and Prophetic Spirituality in the Old Testament: A Theological Integration of Ministry and Proclamation - Mawikere, Marde Christian Stenly; Hura, Sudiria; Mawikere, Jean Calvin Riedel; Mawikere, Daniella Beauty Melanesia (Sekolah Tinggi Teologi Transformasi Indonesia, 2025)
Abstract:This study investigates the interwoven dimensions of prophetic spirituality, ministry, and the proclamation of tiqvah le-mashiach (תִּקְוָה לַמָּשִׁיחַ)—the hope of the Messiah—within the theological framework of the Hebrew Scriptures. It examines how prophetic experiences, such as divine visions and vocational struggles, shaped their roles as mediators of God's will and as heralds of justice, repentance (teshuvah / תְּשׁוּבָה), and covenant renewal. Through a qualitative and hermeneutical approach, the research engages in a theological analysis of selected prophetic texts, particularly from the books of Isaiah (Yeshayahu / יְשַׁעְיָהוּ) and Jeremiah (Yirmeyahu / יִרְמְיָהוּ), uncovering a rich spiritual tradition grounded in unwavering obedience, moral reform, and eschatological hope. The findings reveal that prophetic spirituality was not an isolated religious experience but a deeply embodied response to divine calling, marked by a commitment to mishpat (מִשְׁפָּט – justice), chesed (חֶסֶד – steadfast love), and tsedeq (צֶדֶק – righteousness). The Messianic prophecies articulated by the prophets are shown to be both historically situated and theologically enduring, expressing a vision of restoration, sacrificial leadership, and divine sovereignty. This study contributes to ongoing theological discourse by emphasising the enduring relevance of prophetic witness and offering a framework for integrating spirituality, ministry, and eschatology in contemporary faith contexts. Its distinctive contribution lies in its integrative theological reflection, which views prophetic ministry as a model for transformative spiritual engagement.